Genetic Advance and Grain Yield Stability of Moroccan Durum Wheats Grown under Rainfed and Irrigated Conditions - Abdelali Boussakouran; Mohamed El Yamani; El Hassan Sakar; Yahia Rharrabti (International Journal of Agronomy)
The development of high-yielding durum wheat genotypes requires the knowledge of the genetic variation for grain yield and its components. This study was performed to determine genetic gain and to evaluate the genotype × environment effect for grain yield and related traits in Moroccan durum wheat. A historical series of varieties developed during the last three decades was grown under two water regimes (rainfed and irrigated) during three growing seasons. Traits evaluated in the present work included grain yield, spikes per m2, kernels per spike, spikelets per spike, kernels per spikelet, spike length, kernel weight, plant height, harvest index, and fertile tillering. Results from ANOVA analyses revealed that grain yield and related traits were controlled to a large extent by water regime and growing season. Grain yield advance per year was estimated in 78 kg ha−1 under irrigated conditions, with no significant change under rainfed ones. Overall, the results indicated that most of the yield components changed by breeding activities during the last three decades. AMMI and joint regression analyses revealed that intermediate varieties have a wide adaptation, and old varieties were specifically acclimated to water-limit environments, while modern varieties were performed only under favorable conditions.